Gambaran Perilaku Perawat dalam Melakukan Kepatuhan Pemilahan Sampah Medis - Melia, Stephanie; Sinaga, Anni; Yulianti, Fransiska (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2024)
According to the World Health Organization (WHO) report in 2014, the non-compliance of healthcare workers in managing medical waste, especially sharps, has had serious consequences. More than 66,000 healthcare workers were infected with Hepatitis B, 16,000 with Hepatitis C, and 200-5000 with HIV. In Indonesia, the Ministry of Health in 2020 reported that only 42.64% of healthcare workers complied with medical waste management standards in 2019. Non-compliance in the segregation of medical waste can pose a threat to the environment, patient safety, and healthcare workers.This research aims to evaluate the compliance behavior of nurses in the segregation of medical waste at St. Antonius Pontianak Hospital. The research method is quantitative with a descriptive approach. The study population includes 228 nurses in the inpatient ward of St. Antonius Pontianak Hospital. A sample of 107 nurses was selected using cluster random sampling. The research instrument is a questionnaire that has been validated and tested for reliability. The research results show that the majority of nurses have good knowledge (93%) and a positive attitude (91%) towards the segregation of medical waste. Additionally, 80% of nurses demonstrated good compliance behavior in the practice of medical waste segregation. In conclusion, the majority of nurses at St. Antonius Pontianak Hospital have good knowledge, attitude, and compliance behavior in medical waste segregation. A recommendation that can be made is the need for regular supervision schedules to ensure nurse compliance in the proper management of medical waste. This is crucial for maintaining patient safety, healthcare worker safety, and a healthy work environment.